An Expression of Fear Realized in the Form of Sentences in the “Stranger Things” Movie - Arbain Arbain (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This study aims to investigate the types and functions of expressions of fear realized in the form of sentences. With a special context in horror movies, the researcher attempted to reveal the types and functions of fear expressions such as directive, commissive, expressive, assertive, and declarative. This research focuses on the subtitles of the Stranger Things season 1 series with 8 episodes, one of the best-selling serial films on the Netflix application. As research aids, the researcher used the Aegisub application and live transcript to ensure the accuracy of speech data. Findings suggest the dominance of the use of directive speech acts as a form of expression of fear. Then, commanding speech is the function of most utterances found as an expression of fear. This study concludes that expressions of fear realized in sentences do not only exist in expressive speech acts but also in other speech acts such as directive, assertive and commissive.